Surface Micro Discharge–Cold Atmospheric Pressure Plasma Processing of Common House Cricket Acheta domesticus Powder: Antimicrobial Potential and Lipid-Quality Preservation - Pina-Pérez, Maria C.; Rodrigo, Dolores; Ellert, Christoph; Beyrer, Michael (Frontiers in Bioengineering and Biotechnology, 2021)
The growing world population and the need to reduce the environmental impact of food production drives the exploration of novel protein sources. Insects are being cultivated, harvested, and processed to be applied in animal and human nutrition. The inherent microbial contamination of insect matrices requires risk management and decontamination strategies. Thermal sterilisation results in unfavourable cooking effects and oxidation of fatty acids. The present study demonstrates the risk management in Acheta domesticus (home cricket) powder with a low energy (8.7—22.0 mW/cm^2, 5 min) semi-direct surface micro discharge (SMD) cold atmospheric pressure plasma (CAPP). At a plasma power density lower than 22 mW/cm^2, no degradation of triglycerides (TG) nor increased free fatty acids (FFA) content was detected. For mesophilic bacteria, 1.6±0.1 log_10 reductions were achieved and for Enterobacteriaceae, close to 1.9±0.2 log_10 reductions in a layer of powder. Colonies of Bacillus cereus, Bacillus subtilis and Bacillus megaterium were identified via the mass spectral fingerprint analysed with matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry (MS). The spores of these Bacillus strains resisted to a plasma power density of 22 mW/cm^2. Additional inactivation effects at non-thermal, practically non-oxidative conditions are supposed for low-intensity plasma treatments combined with the powder’s fluidisation.